Characteristics of a liquid microlayer formed by a confined vapor bubble in micro gap boiling between two parallel plates. (May 2015) - Zhang, Yaohua; Utaka, Yoshio
Abstract: The microlayer thickness formed between an elongated bubble and the heating surface during boiling in a parallel microchannel was measured directly using the laser extinction method. Microchannels with gap sizes of s  = 0.15, 0.30, and 0.50 mm were used as test channels. Water, ethanol, toluene, and HFE7200 were used as testing fluids. The effects of gap sizes, the velocity of the bubble forefront, and the distance from the bubble inception site were investigated. Furthermore, the progress of bubble growth in two dimensions with acceleration was simulated by the volume of fluid ( VOF ) method using the computational fluid dynamics (CFD) package of FLUENT12.1. The microlayer thickness calculated from the simulation results shows relatively good agreement with the experimental results. The effects of the physical properties on the configuration of the microlayer were analyzed, and the characteristics of the microlayer in low- and high-velocity regions were qualitatively clarified. An empirical correlation for the microlayer thickness as the function of the Capillary number, the Weber number, and the Bond number in parallel mini/microchannels was proposed using dimension analysis. The present correlation predicts the experimental results within an accepted error range.